Thermal Degradation Study of Waste Polymer Matrix Polypropylene and Polyvinyl Chloride as Polymer Matrix Filled Rice Husk Decking Structure - Afiqah S., N.; Zafiah M. Rus, Anika; N. Aisyah Abdullah, A.; Shahrizan Syah, A.; Hazwanee M. J., Farhana; M, Noraini; Aida I, S (International Journal of Engineering and Technology, 2018)
The aim of this study is to find another alternative material to replace the additives of polymeric materials. From previous works, woodchips are used to act as filler instead of rice husk. Thus, in this case, the woodchips is being exchange with rice husk and mixed with the waste polymer in order to reduce the cost. This study is about the effect of thermal towards the mechanical and physical properties of this WPC. Therefore, heat test and UV Irradiation Exposure test were conducted on this wood polymer composite (WPC). Then, three parameters were being examined which were difference in density, hardness and physical properties after undergoing heat test and UV Irradiation Exposure test. The density and hardness appearances from both test only had slightly reduction and it can be considered as negligible. The physical changes were not too apparent such as crack that would lead to failure even after being heated and exposed to the UV light for a long period. Thus, it proves that rice husk could replace woodchips in order to be used as decking structure.Â Â